An Adjustment of Certification System of Agricultural Product of Thailand: Case of Rice Seed / การปรับระบบการรับรองมาตรฐานสินค้าเกษตรของประเทศไทย: กรณีเมล็ดพันธุ์ข้าว - มาฆะสิริ เชาวกุล, Makasiri Chaowagul / (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 1 (2559): January - April 2016, 2016)
บทคัดย่อ      ความต้องการเมล็ดพันธุ์ข้าวของประเทศไทยของปีเพาะปลูก 2555-2557 ประมาณการเฉลี่ยได้เท่ากับ 1.122 ล้านตันต่อปี เป็นเมล็ดพันธุ์ที่จำหน่ายอยู่ในท้องตลาดกว่าร้อยละ 60 ที่เหลือเป็นเมล็ดพันธุ์ของเกษตรกร มีเพียงร้อยละ 12 ของเมล็ดพันธุ์ทั้งหมดเท่านั้นที่ผ่านการรับรองมาตรฐานอย่างเป็นทางการ ประมาณร้อยละ 48 ของเมล็ดพันธุ์ที่จำหน่ายในท้องตลาดผลิตโดยร้านค้ารายย่อยที่กระจายอยู่ทั่วประเทศ โดยเฉพาะในจังหวัดที่เป็นพื้นที่ชลประทาน แต่ยังไม่มีกระบวนการที่มีประสิทธิภาพมารับรองมาตรฐานของเมล็ดพันธุ์ส่วนนี้ บทความนี้เป็นส่วนหนึ่งของโครงการศึกษา 2 โครงการ คือ การพัฒนาระบบรับรองมาตรฐานเมล็ดพันธุ์ข้าวแบบมีส่วนร่วมของจังหวัดชัยนาท และโครงการศึกษาการผลิตเมล็ดพันธุ์ข้าวให้ได้มาตรฐานภายใต้พันธมิตรธุรกิจ วัตถุประสงค์หลักของบทความนี้ คือ การนำเสนอกระบวนการพัฒนาระบบรับรองมาตรฐานเมล็ดพันธุ์ข้าวที่กระบวนการผลิต เน้นที่การรับรองมาตรฐานแปลงปลูกเมล็ดพันธุ์ข้าว จากระบบปัจจุบันที่รับรองที่ผลผลิต ขั้นสุดท้ายเพียงอย่างเดียว ขั้นตอนการพัฒนาระบบการรับรองมาตรฐานแปลงแบ่งเป็น 4 ขั้นตอน คือ ขั้นตอนการเตรียมการ ทั้งการเตรียมแบบประเมินแปลงและการพัฒนาและเพิ่มจำนวนคนตรวจแปลงมืออาชีพ ขั้นตอนที่ 2 คือ การทดลองปฏิบัติ โดยเกษตรกรจำนวน 60 คนของจังหวัดชัยนาทได้ทดลองใช้แบบตรวจประเมินที่พัฒนาขึ้นกับการตรวจประเมินแปลงปลูกเมล็ดพันธุ์ข้าวของตน ตลอดช่วงการผลิต ขั้นตอนที่ 3 คือ การติดตามและประเมินผลการทดลองปฏิบัติในขั้นตอนที่ 2 ผลผลิตของ 3 ขั้นตอนนี้ คือ แบบตรวจประเมินแปลงที่ผ่านการปรับปรุงและพร้อมที่จะนำไปใช้ตรวจประเมินแปลงปลูกเมล็ดพันธุ์ข้าวจริง ซึ่งเป็นขั้นตอนที่ 4 ซึ่งพื้นที่ปฏิบัติการอยู่ในจังหวัดพิจิตร และสุพรรณบุรี กลุ่มตัวอย่างที่เข้าร่วมโครงการในขั้นตอนนี้ คือ ร้านค้าและเกษตรกรลูกแปลงของร้านค้า จำนวน 65 คน จำนวนแปลงปลูกและพื้นที่ปลูกเท่ากับ 91 แปลงและ 1,418 ไร่ ตามลำดับ ผลการศึกษา พบว่า หลังจากการตรวจประเมินแปลง 3 ครั้งต่อแปลง จำนวนพื้นที่ที่ผ่านมาตรฐานแปลงเพิ่มขึ้นจากร้อยละ 24.61 จากการตรวจประเมินแปลงครั้งที่ 2 มาเป็นร้อยละ 75.39 จากการตรวจแปลงครั้งที่ 3 ผลการศึกษาชี้ว่า ตัวแปรสำคัญที่ทำให้การนำระบบการรับรองมาตรฐานแปลงปลูกเมล็ดพันธุ์ข้าวไปสู่การผลิตเมล็ดพันธุ์ข้าวเชิงพาณิชย์ คือ (1) การเพิ่มจำนวนคนตรวจประเมินแปลงที่มีศักยภาพในการตรวจประเมินแปลงเทียบเท่าเจ้าหน้าที่ของกรมการข้าวที่เพียงพอ ที่อาจจะเป็นเกษตรกรหรือผู้ประกอบการที่มีประสบการณ์ในการผลิตเมล็ดพันธุ์ข้าวมาพอสมควร (2) ลักษณะของแบบประเมินแปลงปลูกเมล็ดพันธุ์ข้าวที่นอกจากจะต้องครอบคลุมเกณฑ์มาตรฐานแปลงของ GAP Rice Seed แล้ว ยังต้องเป็นแบบประเมินที่ไม่ยากต่อการทำความเข้าใจและสะดวกต่อการใช้ประเมิน (3) ตารางมาตรฐานแปลงเป็นเครื่องมือสำคัญที่ทำให้ผู้ตรวจประเมินแปลงสามารถประเมินได้ทันทีว่าแปลงผ่านมาตรฐานหรือไม่หลังจากการตรวจแปลงได้เสร็จลง ข้อเสนอแนะของโครงการศึกษา คือ ไม่เพียงแต่ความเพียงพอของคนตรวจแปลงเท่านั้น แต่กรมการข้าวควรพิจารณากระบวนการขึ้นทะเบียนรับรองคนตรวจแปลงมืออาชีพ เพื่อเพิ่มการยอมรับผลของการตรวจประเมินแปลงของคนตรวจแปลง   คำสำคัญ : เมล็ดพันธุ์ข้าว  ระบบรับรองมาตรฐาน  คนตรวจแปลง  มาตรฐานแปลง   Abstract The estimated demand for rice seed in Thailand on 2012–2014 crop year was averaged at 1.122 million tons per year where approximately 60% was sold in the market while the remaining was farmers’ own rice seed. Only 12% of the total rice seed was formally certified. It was 48% of those rice seed in the market was produced by small local enterprises located all over the country, especially in the irrigated area. However, there was no efficient process yet for certifying this portion of seed at present. This paper was a part of two study projects. Part I was the participatory development of standard certification system for rice seed of Chainat province and Part II was the production of standardized rice seed under the business partnership. The main objective of this paper was to present the development process of rice seed certification system at the production process focusing on the rice seed field certification, where the present certification is the product certification only. There were 4 steps in developing the rice field certification system process. The first step was the preparation of both rice seed field evaluation form and development and increasing number of professional field inspectors. The second step was an experiment and evaluation using the developed evaluation form by 60 farmers in Chainat province for inspecting their rice seed fields through 1 crop production. The third step was monitoring and evaluation. The output of these 3 steps was the adjusted evaluation form of rice seed field which was ready to use for evaluation the real rice seed field. This adjusted evaluation form was used in the fourth step where the implementing areas were at Suphanburi and Phichit provinces. The participants of this step included the small local enterprises and their 60 farmers producing rice seed for them. The number of fields and cultivated area were 91 fields and 1,418 rais, respectively. It was found that after 3 inspections per field of the cultivated are as, the field standard increased from 24.61% in the second field inspection to 75.39%. The results of the study indicated that the key success factors of raising this rice field certification system to the rice seed production at commercial level would be: (1) the increase of professional rice seed field inspectors and evaluators with equivalent quality of inspection to those of the national level. These professional inspectors could be either potential farmers or local enterprises who had experience in producing rice seed for quite some time, (2) rice seed field evaluation form should not only cover all field standard criteria of GAP Rice Seed, but should also be easy and convenient to use, (3) the rice seed field standard table was an important instrument for deciding whether or not the rice seed field would pass the field standard right after the inspection ended. This study suggested that not only the sufficiency of the potential field inspectors and evaluators, but the department of rice should consider the process of registration of professional inspector and evaluator as well to increase degree of acceptance in evaluating results.     Keywords : Rice Seed, Certification System, Field Inspector, Field Standard
Keywords: การปรับระบบการรับรองมาตรฐานสินค้าเกษตรของประเทศไทย: กรณีเมล็ดพันธุ์ข้าว เมล็ดพันธุ์ข้าว ระบบรับรองมาตรฐาน คนตรวจแปลง มาตรฐานแปลง Rice Seed, Certification System, Field Inspector, Field Standard